"Causality crisis" in acculturation research a false alarm?: A commentary on Kunst (2021). (January 2022) - Grigoryev, Dmitry; Berry, John W.
Abstract: The invited IAIR Award Paper by Kunst (2021) published in IJIR asserts that there is a "causality crisis" in acculturation research and critically discusses the current meta-analytical evidence supporting the integration hypothesis. In this commentary, we question this claim in light of our understanding of the acculturation process and its constituent phenomena. Our proposal is to consider acculturation patterns as behavioral syndromes, in which many phenomena are inter-related and which change over the course of acculturation. We also question the claim in Kunst's paper about meta-analytical evidence, and end with some proposals for future research on acculturation.